Spatial extent of plasmonic enhancement of vibrational signals in the infrared - Neubrech, Frank; Beck, Sebastian; Glaser, Tobias; Hentschel, Mario; Giessen, Harald; Pucci, Annemarie (ACS nano, 2014)
Infrared vibrations of molecular species can be enhanced by several orders of magnitude with plasmonic nanoantennas. Based on the confined electromagnetic near-fields of resonantly excited metal nanoparticles, this antenna-assisted surface-enhanced infrared spectroscopy enables the detection of minute amounts of analytes localized in the nanometer-scale vicinity of the structure. Among other important parameters, the distance of the vibrational oscillator of the analyte to the nanoantenna surface determines the signal enhancement. For sensing applications, this is a particularly important issue since the vibrating dipoles of interest may be located far away from the antenna surface because of functional layers and the large size of biomolecules, proteins, or bacteria. The relation between distance and signal enhancement is thus of paramount importance and measured here with in situ infrared spectroscopy during the growth of a probe layer. Our results indicate a diminishing signal enhancement and the effective saturation of the plasmonic resonance shift beyond 100 nm. The experiments carried out under ultra-high-vacuum conditions are supported by numerical calculations.